Preterm vaginal en caul delivery in a case of severe oligohydramnios with pyelonephritis - Ghosh, Kashmira; Choudhury, Arun Paul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
En caul deliveries are very rare and are associated with prematurity. Approximately 40 percent of spontaneous premature births are thought to be caused by infection. Preterm along with oligohydramnios can lead to en caul delivery. We report a case of 27-year-old gravida 4 multiparous women with a history of 2 normal vaginal deliveries NSVD and 1 spontaneous abortion, who presented at 32 weeks of gestation in active labour and delivered preterm viable female with an intact placenta contained within the amniotic sac as a unit “en caul.” Since the patient gave a history of lower back pain with burning micturition for 1 month which remained consistent after delivery, ultrasonography whole abdomen was done and bilateral pyelonephritis was diagnosed. However, the baby’s sepsis screen was negative and discharged healthy. We report this case because of its rarity of occurrence and to show that intact amniotic membrane during birth can protect the baby from birth trauma and infections.